2011
DOI: 10.1051/0004-6361/201015749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the radial flows on the chemical evolution of the Milky Way disk

Abstract: Context. The majority of chemical evolution models assume that the Galactic disk forms by means of infall of gas and divide the disk into several independent rings without exchange of matter between them. However, if gas infall is important, radial gas flows should be taken into account as a dynamical consequence of infall. Aims. We test the effects of radial gas flows on detailed chemical evolution models (one-infall and two-infall) of the Milky Way disk with different prescriptions for the infall law and sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(160 citation statements)
references
References 37 publications
8
150
1
1
Order By: Relevance
“…In the light of our results, the thick disk rotation-metallicity correlation (Spagna et al 2010;Lee et al 2011) seems to represent an important signature of the disk evolution. This feature can indeed be explained by the role of the dynamical migration in our N-body simulations, once we assume an initial radial chemical gradient as that suggested by the chemical evolution models of Spitoni & Matteucci (2011), which prescribes a positive slope for the inner early disk, R < ∼ 10 kpc, combined with the usual decreasing slope in the outer disk. The crucial role of a positive inner slope for the primordial chemical distribution to produce a positive rotation-metallicity correlation was presented in Curir et al (2012), where a distribution consisting of two simple linear functions with positive slope for inner radii up to 6 kpc and a negative one outwards was plugged in the early (N-body) disk 3 .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the light of our results, the thick disk rotation-metallicity correlation (Spagna et al 2010;Lee et al 2011) seems to represent an important signature of the disk evolution. This feature can indeed be explained by the role of the dynamical migration in our N-body simulations, once we assume an initial radial chemical gradient as that suggested by the chemical evolution models of Spitoni & Matteucci (2011), which prescribes a positive slope for the inner early disk, R < ∼ 10 kpc, combined with the usual decreasing slope in the outer disk. The crucial role of a positive inner slope for the primordial chemical distribution to produce a positive rotation-metallicity correlation was presented in Curir et al (2012), where a distribution consisting of two simple linear functions with positive slope for inner radii up to 6 kpc and a negative one outwards was plugged in the early (N-body) disk 3 .…”
Section: Discussionmentioning
confidence: 56%
“…Radial flows were not considered 1 . The model adopted in this paper is Model S2IT of Spitoni & Matteucci (2011), their Table 1: it is a two-infall model similar to that presented in Chiappini et al (2001) and Cescutti et al (2007). This particular model was chosen because it accurately reproduces the most recent estimate of the present time abundance gradients by Luck & Lambert (2011) in a galactocentric range 4-14 kpc.…”
Section: Chemical Distributionmentioning
confidence: 99%
“…In this work, we did not explore different values of the threshold in the halo, our aim being to test the effects of the enriched infall on chemical evolution models of the MW, which are able to reproduce the majority of the observations in the solar neighbourhood and also the abundance gradients along the disc. As shown in Mott, Spitoni & Matteucci (2013), if we do not take into account radial gas flows (Portinari & Chiosi 2000;Spitoni & Matteucci 2011;Cavichia et al 2014), a threshold in the gas density is required to explain the abundance gradients along the Galactic disc, and in particular the values of 4 M pc −2 in the halo phase and 7 M pc −2 in the thin disc phase, provide a very good agreement with the data.…”
Section: The Results: the Galactic Halo In The Model 2immentioning
confidence: 64%
“…Curir et al (2012) linked this to inverse metallicity gradients (i.e. larger metallicities in the outer regions of a disc) at early times, identified in the chemical evolution models of Spitoni & Matteucci (2011) and Chiappini et al (2001), as well as occasionally observed in high-redshift galaxies, such as those studied by Cresci et al (2010).…”
Section: Introductionmentioning
confidence: 74%